Experimental observation of geometric effect on the electron diffraction of quasi-one-dimensional nanostructures. (April 2023) - Zhang, Tongxie; Eaton, Adam T.; Mukherjee, Dibya K.; Cao, Michael; Coughlin, Amanda L.; Ruch, Thomas; Zhan, Xun; Zhu, Hanyu; Han, Yimo; Fertig, Herbert A.; Zhang, Shixiong
Abstract: One-dimensional (1D) nanostructures, such as nanowires, constitute building blocks for nanoscience and nanotechnology. Their fundamental physical properties are dictated by their crystalline structures, which are often characterized by transmission electron microscopy (TEM). Theoretically, the shape of a nanostructure can affect its electron diffraction pattern; however, for 1D nanostructures, an experimental observation of this geometric effect has not been reported. Here, we demonstrate unambiguously the first experimental observation of this geometric effect in electron diffraction from nanowires of iridium dioxide (IrO2 ) and lead tin telluride (Pb1-x Snx Te), which are topological semimetals and topological crystalline insulators, respectively. Grown by chemical vapor deposition, the nanowires are single-crystalline and have well defined facets with nearly rectangular cross-sections. Diffraction spot splitting was observed in electron diffraction patterns when the e-beam was not perpendicular to the major facets of the nanowires. Atomic-resolution scanning TEM studies rule out other possible origins of the splitting, including twin domains and non-uniform strain. Theoretical calculations of electron diffraction capturing the nanowire geometry show good agreement with the experimental results, including the diffraction order dependence of the peak splitting. The observation of this geometric effect offers a non-destructive approach to characterizing the thickness of the one-dimensional nanostructures.